ANALISIS PERANCANGAN METODE VLSM DAN FLSM PADA MANAJEMEN IP ADDRESS LAN - Rahman, Nur; Santoso, Banu; Pambudi, Agung; K Rasyid, Rum Mohamad Andri; Mulyatun, Sri; Tegris, Efrat; Widya Sari, Marti (Universitas PGRI Semarang, 2024)
Computer networks are very important for people in the current era of modern globalization to access their daily needs. A good computer network is certainly needed to speed up community activities. Sub-netting is one of the things that can be done to optimize IP management on a computer network. This research on the application of the subnetting method on a computer network can be a reference in determining a better subnetting method for building a network. This research aims to analyze the influence of the two subnetting methods on a computer network, compare the network speeds obtained, and the application of the two subnetting methods on a computer network based on QoS parameters. The research results show that the analysis of both subnetting methods displays a very good QoS Index with the following details: FLSM: average throughput 50.792kbps, packet loss 0%, average delay 5.25ms, average jitter 5.37ms. VLSM: average throughput 77.843kbps, packet loss 0%, average delay 3.52ms, average jitter 3.58ms. In the FLSM method, all applied subnets have 101 remaining unused IPs and in VLSM, all applied subnets have 19 unused IPs remaining. This proves that networks designed using the VLSM subnetting method have more optimal network quality and more effective IP management.